Evaluation of Nutritional Value, Consumer Preference and Profitability of Orange-Fleshed Sweetpotato Puree Incorporated Bread and Injera - Mengesha, A.K.; Bassore, D.G.; Endrie, S.G.; Brouwer, R. (Wiley, 2023)
Incorporation of OFSP puree into wheat flour bread and teff flour injera can enrich the β-carotene content of the products. Information about the optimal proportion of OFSP puree to be mixed with wheat and teff flour to make bread and injera is currently lacking in Ethiopia. This study was carried out to determine the optimum proportion of OFSP puree to be incorporated into wheat flour bread and teff flour injera, and to evaluate the nutritional content, sensory acceptability, and profitability of OFSP-blended wheat bread and teff injera. Four OFSP puree: wheat flour ratio (0:100, 15:85, 30:70 and 45:55) and four OFSP puree: teff flour ratio (0:100, 15:85, 30:70 and 45:55) were evaluated. Significant differences (P<0.05) were found for β-carotene content among the four bread and injera treatments. The highest β-carotene (2340 ug 100 g-1 and 1735.00 μg 100 g-1) content was found in the bread and injera blended with 45% OFSP puree, respectively. Marked differences were also found among bread treatments with overall acceptability scores of 6.22 (100% wheat flour bread) and 5.93 (15% OFSP puree blended bread). Similarly, overall sensory acceptability varied profoundly among injera treatments with the highest scores of 5.73 and 5.85 recorded for injera blended with 15% and 30% OFSP puree, respectively. Considering the higher β-carotene content and sensory qualities, bread and injera made from wheat and teff flour blended with 30% OFSP puree is recommended for commercial production and consumption among urban and rural consumers including the most vulnerable groups to vitamin A deficiency.